Postsecularism and contemporary spirituality - Jasiński, Karol (Array, 2020)
The author of the article attempted to define the character of contemporary, new form of spirituality and show its connections with religion. The appearance of a new kind of spirituality is the result of processes taking place in social life. On the one hand, it is marked by secularization and secularism, on the other, it is desecularization and post-secularism. The analyzes were based on the belief that a new spirituality alone is insufficient in the life of a particular man, but it must find a complement to some religion. The article consists of three parts. In the first one the following phenomena were discussed: secularization, secularism, post-secularism. The second part analyzes the phenomenon of new spirituality. In the third, however, attention was drawn to the issue of religion, the traditional understanding of spirituality and the nature of the relationship between religion and spirituality.